2019
DOI: 10.3390/ma12060973
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Temperature on the Burst Process of Carbon Fiber/PVA Fiber High-Strength Concretes

Abstract: This paper carried out burst tests on the carbon and polyvinyl alcohol (PVA) fiber high-strength concrete specimens to investigate the effects of fiber type, fiber content, water content, heating rate and test specimen size on the burst, and the whole burst process of fiber-high concrete was photographed and recorded. The results indicated that fiber addition will improve the high temperature burst behavior of the high-strength concrete, and the performance of PVA is greatly different from that of carbon fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This may be attributed to the fiber bridging effect, or in other words, when concrete exposed to high temperature, the PVA fibers melts creating paths to escape water vapor, which was captured in pore structure of concrete, in order to give concrete room to breathe, to prevent explosions and, in turn, to increase its resistance (Osman et al, 2019). Cao et al (2019) also observed no spalling in samples with PVA exposed to elevated temperature. Figure 7 shows the load deflection relations for specimens including different PVA ratios and subjected to different overheating time durations at zero eccentricity.…”
Section: Load-deflection Curves For Studied Columnsmentioning
confidence: 96%
See 2 more Smart Citations
“…This may be attributed to the fiber bridging effect, or in other words, when concrete exposed to high temperature, the PVA fibers melts creating paths to escape water vapor, which was captured in pore structure of concrete, in order to give concrete room to breathe, to prevent explosions and, in turn, to increase its resistance (Osman et al, 2019). Cao et al (2019) also observed no spalling in samples with PVA exposed to elevated temperature. Figure 7 shows the load deflection relations for specimens including different PVA ratios and subjected to different overheating time durations at zero eccentricity.…”
Section: Load-deflection Curves For Studied Columnsmentioning
confidence: 96%
“…The inclusion of steel fibers, in the hybrid fiber samples reduced mass loss from the samples at 600 o C. He also noted that after exposure to temperatures beyond 150 o C (near the melting point of the fibers), the failure mode of samples with PVA fibres changed from rupture to pulling out resulting in the change of behaviour of samples from deflection hardening to deflection-softening behavior. In another investigation, Cao, et al (2019) compared the residual mechanical properties for high strength samples (> 85MPa), containing PVA or Carbon fibers or both after exposure to 800 o C for up to 260 minutes. They concluded that the inclusion of the PVA in the samples can enhance the flexural strength and splitting strength of the concrete, but has little influence on the axial compressive strength when exposed to elevated temperatures.…”
Section: Effect Of Elevated Temperatures On Specimens Including Pva Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The melting point of PVA fiber is reported to be between 220 and 230 °C [ 216 , 217 , 218 ]. Heo et al [ 107 ] utilized PP, PVA, and nylon fibers with different lengths and volume fractions in concrete to evaluate their efficiency when exposed to elevated temperatures.…”
Section: Extreme Temperature Resistancementioning
confidence: 99%
“…e existing literature shows that the application of PVA fiber in concrete has great potential and value. So far, the related research studies of PVA fiber concrete are mainly focused on the basic mechanical properties [7][8][9][10][11], bending behavior [12][13][14], impact properties [11,15], mechanical properties under the freeze-thaw cycle [16][17][18], and high-temperature properties [19][20][21][22][23], while the damped energy dissipation characteristics concerned by engineering seismic research are less studied [24].…”
Section: Introductionmentioning
confidence: 99%